STRATEGI PROMOSI DAN PUBLIKASI SMP PGRI 363 PONDOK PETIR DI MASA PANDEMI COVID 19 - Budiastuti, Dewi Retno (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
As a formal place for students to receive education and knowledge, schools are expected to provide quality and facilities that assist students in receiving the best education possible.The development of internet technology also helps students to get the knowledge and references needed to support learning. If students can get information from various sources, then as a school institution, SMP PGRI 363 is expected to be the main source for students to get education and knowledge. This study uses qualitative research methods. The research was conducted at SMP PGRI 363 Pondok Petir, which is located on Jl. Reni Jaya Selatan, Pondok Lightning, Kec. Bojongsari, Depok City, West Java. Qualitative research uses a theoretical basis and also uses general questions, which then become a reference and more details on the phenomena that occur in the field. The promotion and publication strategies carried out by SMP PGRI 363 Pondok Petir during the Covid 19 pandemic included picking up the ball to the target school, providing brochures, pamphlets, installing banners, free building fees for wave 1, conducting a database of the student's homeroom cell phone number for the target school, make online registration video tutorials, and make video school activities videos. The promotion and publication strategy produced results at PPDB in 2021, it can be seen from the number of students who registered at 86 students, which increased by 43% from the previous year. SMP PGRI 363 Pondok Petir is expected to be able to further activate the school's social media for promotion and school publications. It can also be reached by local media in the city of Depok to be able to announce and inform about the advantages of SMP PGRI 363 Pondok Petir.